Legal Education at a Crossroads: Innovation, Integration, and Pluralism Required! - Karen Tokarz; Antoinette Sedillo Lopez; Peggy Maisel; Robert F. Seibel (Washington University Journal of Law & Policy, 2014)
Although historically slow to change, law schools are now facing enormous pressure from educators, students, lawyers, judges, clients, and the public to rethink legal education and the lawyer‘s role in society. Now more than ever, there is robust national debate on the threshold contributions law schools should make to the preparation of law graduates for entry into practice. The clamor for reform in legal education is precipitated by a confluence of factors, including new insights about lawyering competencies and experiential legal education; the shifting nature of legal practice in the United States; a decrease in law jobs; changes in the economics of the legal profession that challenge the current cost of legal education; a dramatic drop in law school applications and admittees; increased competition for students among law schools; increased market demand for ―practice-ready‖ law graduates; and increased numbers of law grads going into solo and small firm practice. Economic, social, and political conditions make it impossible to ignore the clamor for reform. Today‘s climate invites a deeper examination of law school curricula and pedagogy, with a focus on the "sequencing of doctrine, skills and values across the curriculum designed to prepare students for practice . . . ." Legal education is at a crossroads, uniquely ripe for innovative curricular and pedagogical change. Some suggest abandoning the third year of law school; others urge law schools to accept the challenge from educators, the profession, and the market to impart more educational value throughout the curriculum, including the third year. Educating Lawyers: Preparation for the Profession of Law, the influential study produced by the Carnegie Foundation for the Advancement of Teaching in 2007 (commonly referred to as the "Carnegie Report"), endorses a three-year curriculum that develops the three lawyering apprenticeships of knowledge/understanding, practice expertise, and professional identity/judgment. In this Article, we recommend an innovative, integrated, pluralistic law school curriculum with expanded experiential education (where students learn in the role of attorney with simulated clients and cases) and required clinical education (where students learn in the role of attorney with real clients and cases).
Keywords: legal education reform; legal education; clinical education; legal clinics